O impulso ao mercado de capitais no Brasil: uma avaliação do novo mercado da BOVESPA sob a perspectiva institucionalista - Gomes, Mauricio Valongo (2009)
The purpose of this dissertation is to analyze the contribution of the BOVESPA S Novo Mercado creation for the Brazilian capital market development. In order to support this study, the research intended to reach a greater understanding about the determinants of capital raise activity via capital market as a source of long-term funds for companies, based on authors researches from New Institutional Economics. The analysis of institutional changes effects from Novo Mercado on the capital market was made in two analytical sections: macro and micro. In the macro view, we found a rising on the levels of market size and maturity indicators in terms of market value, volume transacted and amount of resources raised by the companies through securities public offerings. In the micro analysis, we tried to identify a relationship between the listing of companies in one of the BOVESPA'S corporate governance listing segments - Levels 1 and 2 and Novo Mercado - and its value. For this, using the indicator "Tobin s Q", we made a comparative analysis of listed companies value in different segments of corporate governance with the BOVESPA'S traditional listing segment for the period from 2004 to September 2008 and a regression analysis to test the effect of the companies' adhesion to the corporate governance listing segments on the companies' value